Pharmacokinetic and bioequivalence study comparing a fimasartan/rosuvastatin fixed-dose combination with the concomitant administration of fimasartan and rosuvastatin in healthy subjects - Kang WY (Drug Design, Development and Therapy, 2018)
Woo Youl Kang,1,2,* Sook Jin Seong,1,2,* Boram Ohk,1,2 Mi-Ri Gwon,1,2 Bo Kyung Kim,1,2 Seungil Cho,1,2 Wang-Seob Shim,3 Kyung-Tae Lee,4 Eun Hee Kim,5 Dong Heon Yang,6 Hae Won Lee,1,2 Young-Ran Yoon1,2 1Department of Molecular Medicine, School of Medicine, Kyungpook National University, Daegu, Republic of Korea; 2Department of Clinical Pharmacology, Kyungpook National University Hospital, Daegu, Republic of Korea; 3Kyung Hee Drug Analysis Center, Kyung Hee University, Seoul, Republic of Korea; 4College of Pharmacy, Kyung Hee University, Seoul, Republic of Korea; 5College of Nursing, Catholic University of Daegu, Gyeongsan-si, Gyeongbuk, Republic of Korea; 6Division of Cardiology, Department of Internal Medicine, Kyungpook National University Hospital, Daegu, Republic of Korea *These authors contributed equally to this work Purpose: A new fixed-dose combination (FDC) formulation of 120 mg fimasartan and 20 mg rosuvastatin was developed to increase therapeutic convenience and improve treatment compliance. Methods: A randomized, open-label, single-dose, two-treatment, two-way crossover study with a 7-day washout period was conducted to compare the pharmacokinetic (PK) characteristics and bioequivalence between an FDC of fimasartan/rosuvastatin and the separate co-administration of fimasartan and rosuvastatin in healthy Korean volunteers. The plasma concentrations of fimasartan and rosuvastatin were analyzed by a validated liquid chromatography-tandem mass spectrometry method, for which serial blood samples were collected for up to 48 hours post-administration of fimasartan and 72 hours post-administration of rosuvastatin, in each period. The PK parameters were calculated using a non-compartmental method. Results: A total of 78 subjects completed the study. All the 90% CIs of the geometric mean ratios (GMRs) fell within the predetermined acceptance range. The GMR and 90% CI for the area under the plasma concentration-time curve from time 0 to the last measurement (AUC0–t) and the maximum plasma concentration (Cmax) for fimasartan were 0.9999 (0.9391–1.0646) and 1.0399 (0.8665–1.2479), respectively. The GMR and 90% CI for the AUC0–t and Cmax for rosuvastatin were 1.0075 (0.9468–1.0722) and 1.0856 (0.9944–1.1852), respectively. Treatment with fimasartan and rosuvastatin was generally well tolerated without serious adverse events. Conclusion: The new FDC formulation of 120 mg fimasartan and 20 mg rosuvastatin can be substituted for the separate co-administration of fimasartan and rosuvastatin, for the advantage of better compliance with convenient therapeutic administration. Keywords: fixed-dose combination, pharmacokinetics, bioequivalence, fimasartan, rosuvastatin